2013
DOI: 10.1002/mc.22084
|View full text |Cite
|
Sign up to set email alerts
|

Emodin modulates epigenetic modifications and suppresses bladder carcinoma cell growth

Abstract: The deregulation of epigenetics was involved in early and subsequent carcinogenic events. Reversing cancer epigenetics to restore a normal epigenetic condition could be a rational approach for cancer treatment and specialized prevention. In the present study, we found that the expression levels of two epigenetic markers, histone H3K27 trimethylation (H3K27me3), was low but histone H3S10 phosphorylation (pH3Ser10) was high in human bladder cancer tissues, which showed opposite expression patterns in their norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
1
26
1
5
Order By: Relevance
“…Emodin significantly inhibited the cell growth of four bladder cancer cell lines by modulating epigenetic modifications in a dose‐dependent and time‐dependent manner (Cha et al ., ). In another study, emodin (IC 50 = 3.70 µ m ) was shown to modulate the expression of apoptosis‐related genes to induce growth inhibition and apoptosis in A549 cells.…”
Section: Pharmacologymentioning
confidence: 97%
“…Emodin significantly inhibited the cell growth of four bladder cancer cell lines by modulating epigenetic modifications in a dose‐dependent and time‐dependent manner (Cha et al ., ). In another study, emodin (IC 50 = 3.70 µ m ) was shown to modulate the expression of apoptosis‐related genes to induce growth inhibition and apoptosis in A549 cells.…”
Section: Pharmacologymentioning
confidence: 97%
“…The phytochemical 1,2,8-trihydroxy-6-methylanthraquinone (emodin), derived from Rheum palmatum , has been shown to be more potent against PCa than curcumin or genistein [95]. The investigators showed that emodin induces dissociation of AR from Hsp90 and increases its interaction with the E3 ligase MDM2, thus promoting the proteasome-mediated degradation of AR in LNCaP cells [95].…”
Section: Natural Products Against Pcamentioning
confidence: 99%
“…The investigators showed that emodin induces dissociation of AR from Hsp90 and increases its interaction with the E3 ligase MDM2, thus promoting the proteasome-mediated degradation of AR in LNCaP cells [95]. Importantly, emodin also promoted AR degradation in tumor tissues and suppressed tumor growth in C3(1)/SV40 transgenic mice with no effect on body weight and physical activity [96].…”
Section: Natural Products Against Pcamentioning
confidence: 99%
“…It has been shown to possess antibacterial, antitumor, anti-inflammatory and vasorelaxant effects (33)(34)(35). Rheum palmatum has long been used for acute intestinal obstruction in China.…”
Section: Introductionmentioning
confidence: 99%